2022
DOI: 10.3390/nu14224923
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Acute Malnutrition Treatment at Health Center and Community Levels with a Simplified, Combined Protocol in Mali: An Observational Cohort Study

Abstract: A simplified, combined protocol was created that admits children with a mid-upper-arm circumference (MUAC) of <125 mm or edema to malnutrition treatment with ready-to-use therapeutic food (RUTF) that involves prescribing two daily RUTF sachets to children with MUAC < 115 mm or edema and one daily sachet to those with 115 mm ≤ MUAC < 125 mm. This treatment was previously shown to result in non-inferior programmatic outcomes compared with standard treatment. We aimed at observing its effectiveness in a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
16
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
6
16
3
Order By: Relevance
“…Our study’s results differ from those reported in the aforementioned Malian cohort in which CHWs with a simplified protocol obtained slightly better recovery results than nurses ( 44 ), highlighting the importance of simplifying the management of cases in complex contexts such as Gao, where there are fewer skilled human resources and CHWs possess less experience and literacy ( 51 , 52 ). Another Malian study highlighted the importance of supportive supervision to ensure the quality of SAM treatment provided by CHWs when the program was scaled to larger regions ( 15 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our study’s results differ from those reported in the aforementioned Malian cohort in which CHWs with a simplified protocol obtained slightly better recovery results than nurses ( 44 ), highlighting the importance of simplifying the management of cases in complex contexts such as Gao, where there are fewer skilled human resources and CHWs possess less experience and literacy ( 51 , 52 ). Another Malian study highlighted the importance of supportive supervision to ensure the quality of SAM treatment provided by CHWs when the program was scaled to larger regions ( 15 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our previous studies in Mali have shown that the decentralization of treatment with CHWs results in lower default rates by reducing geographical and economic access barriers for families ( 17–19 ). In addition, the recovery rates found here for the simplified group (92.9%) were very close to the 92.3% reported in a large Malian cohort of 27,800 children treated in non-emergency settings in the southwest with the same combined, simplified protocol and also involving CHWs as treatment providers ( 44 ). Moreover, in the present study, high recovery rates of over 90% were achieved in the most vulnerable group of children admitted; that is, those weighing less than 5 kg.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, the close follow-up provided in this study after discharge, and the treatment of relapses, probably improved nutritional status until observation at 6 months. In Mali, Kangas et al found that, upon discharge with MUAC ≥ 125 mm, 16•0 % of the children presented a WHZ < -2 (1 % with WHZ < -3) (30) . However, these results were observed in children initially admitted with a MUAC < 125 mm and/or oedema, including 73•3 % of children admitted with a MUAC between 115 mm and 125 mm, who are expected to suffer from less severe malnutrition.…”
Section: Discussionmentioning
confidence: 99%